Bose-Einstein condensation in Hořava-Lifshitz theory. (17th May 2021) - Furtado, J.; Assunção, J. F.; Ramos, A. C. A.
Abstract: In this paper we study the corrections emergent from a Hořava-Lifshitz extension of the complex scalar sector to the Bose-Einstein condensation and to the thermodynamics parameters. We initially discussed some features of the model to only then compute the corrections to the Bose-Einstein condensation. The calculations were done by computing the generating functional, from which we extract the thermodynamics parameters. We also obtained the Lifshitz scaling correction for the critical temperature T c that sets the Bose-Einstein condensation.